(3QSGdI Edi CHj SYjO Hf CHj GdNjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN Yf LedI UfGjY Gddg JYGdi s
(3BNQgG (B:s
(3hGSJgOjg hCJhH Edjg hGSJcajg hCSCdg Cf jbQHfi Edjg s
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCeHQhRjGfG (B(116) s
Keywords: (3GdadSaI hGdefWbs